Analyzing Deformation and Damage of VT1-0 Titanium in Different Structural States by Using Infrared Thermography; Journal of Nondestructive Evaluation; Vol. 35, iss. 3 - Sharkeev Yu. P. Yury Petrovich; Vavilov V. P. Vladimir Platonovich; Belyavskaya O. A. Olga Andreevna; Skripnyak V. A. Vladimir Albertovich; Nesteruk D. A. Denis Alekseevich; Kozulin A. A.; Kim V. M. (2016, 2016)
Title screen